Travel Heaven - Dr. Shilpi Jain; Dr Madhur Jain; Sourabh Kalyan; Piyush Jain; Aditya Sharma (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The objective of this paper is to design and develop a comprehensive online accommodation platform aimed at simplifying the process of listing, searching, and booking accommodations for both travellers and property owners. The platform seeks to address common challenges faced by existing platforms, such as high fees, limited search options, and communication barriers between hosts and guests. To achieve this, the platform integrates features like secure multi-method authentication, advanced search capabilities, a transparent review system, and a robust admin dashboard for platform management. The development methodology follows a web-based architecture using modern technologies, including MongoDB for data storage, Node.js for backend operations, cloud services for scalability. User security and data protection are prioritized through compliance with GDPR and other relevant regulations. Key findings from the feasibility study indicate a growing demand for user-centric, feature-rich platforms in the accommodation sector. This platform is technically and financially feasible and has the potential to enhance user satisfaction by offering a more flexible, secure, and transparent marketplace. The platform aims to become a trusted solution for both travellers and property owners while ensuring adaptability for future growth and market trends.